Progress of the Sustainable Development Goals (SDG) in Costa Rica - González M, María Luisa (2022)
The 2030 Agenda for Sustainable Development, approved in September 2015 by the United Nations General Assembly, establishes a transformative vision towards economic, social and environmental sustainability for the 193 member states that signed it and is the reference guide for the work of the international community until the year 2030. This agenda presents a historic opportunity for Latin America and the Caribbean, since it includes high-priority issues for the region, such as the eradication of extreme poverty, the reduction of inequality in all its dimensions, inclusive economic growth with decent work for all, sustainable cities and climate change, among others. This article reflects on the progress of this initiative in Costa Rica, pondering the main results achieved to date and outlining the main challenges that the country faces.